2012
DOI: 10.1002/qua.24100
|View full text |Cite
|
Sign up to set email alerts
|

Critical analysis of the through‐space transmission of NMRJFHspin–spin coupling constants

Abstract: NMR JFH coupling constants transmitted through space are known to show several unusual peculiarities. The main three are (a) in many cases their experimental values are reported to be positive and in others, negative; (b) theoretical values show that in some cases they are substantially contributed not only from the Fermi contact (FC) term but also from the paramagnetic spin orbit (PSO) term, and their respective signs could be either like or unlike; (c) in many cases it can hardly be expected that the corresp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 28 publications
2
14
0
Order By: Relevance
“…In the solid state, however, it should, in principle, be possible to see intermolecular through-space J couplings, that is, between different molecules, if they are held in close proximity by the crystal packing. The existence of these interactions, and their relative magnitude in simple systems, has been studied computationally. , However, there remain relatively few experimental reports of any through-space J couplings in solids, either intermolecular or intramolecular, in the literature, although some J couplings through intermolecular hydrogen bonding interactions have been observed . Examples of intramolecular through-space couplings observed in the solid state have included the observation of 77 Se– 125 Te and 31 P– 125 Te couplings in peri-substituted naphthalenes, , 11 B– 31 P interactions in frustrated Lewis pairs in alkenes, and 31 P– 31 P interactions in ferrocenes .…”
Section: Introductionmentioning
confidence: 99%
“…In the solid state, however, it should, in principle, be possible to see intermolecular through-space J couplings, that is, between different molecules, if they are held in close proximity by the crystal packing. The existence of these interactions, and their relative magnitude in simple systems, has been studied computationally. , However, there remain relatively few experimental reports of any through-space J couplings in solids, either intermolecular or intramolecular, in the literature, although some J couplings through intermolecular hydrogen bonding interactions have been observed . Examples of intramolecular through-space couplings observed in the solid state have included the observation of 77 Se– 125 Te and 31 P– 125 Te couplings in peri-substituted naphthalenes, , 11 B– 31 P interactions in frustrated Lewis pairs in alkenes, and 31 P– 31 P interactions in ferrocenes .…”
Section: Introductionmentioning
confidence: 99%
“…These results indicate that ED, a property dependent on the pair density, carries information concerning the experimentally measurable NMR indirect coupling constants. Nevertheless, in an NMR study of how J FH indirect coupling constants transmit through space, Tormena et al found cases wherein the FC term can have negative values. However, as the contributions to the delocalization index are positive, the authors pointed out that the relation between the NMR indirect coupling constants and delocalization indexes should be taken with caution.…”
Section: Applications Of Qtaimmentioning
confidence: 99%
“…The importance played by overlap interactions on the through‐space transmission of SSCCs is remarkable; thus, the overlap matrix (S) elements were evaluated using the natural bond orbital (NBO) analysis, implemented in the Gaussian 09 suite of programs. These calculations were performed with the B3LYP hybrid functional using the EPR‐III basis set.…”
Section: Experimental and Computational Detailsmentioning
confidence: 99%
“…Because in all cases, the FC contribution is the most significant one, special emphasis is put in rationalizing its transmission. It is important to recall that recently, it was found that the transmission of the coupling constant nTS J FH SSCCs originates in the competition between the overlaps of the X‐H bond with the C‐F bond and with the F non‐bonding electron pairs. In those cases, the proximity between fluorine lone pair LP 2 (F) and hydrogen atom increases the s % character of the LP 2 (F) playing an important contribution to the through‐space transmission of the FC term for some J FH SSCCs.…”
Section: Introductionmentioning
confidence: 99%